Control of stuttering behaviour through response contingent shocks - J, Bharath Raj (Journal of All India Institute of Speech and Hearing)
Several recent studies have brought stuttering under operant control and shown how it can be manipulated by the consequences it generates. Goldiamond (1965) and his colleagues have demonstrated through their extensive studies, that a very high degree of such control over speech, can be achieved. Using either a high intensity white noise of a 105 dB blast (Flanagan el al. 1958) or DAF (Goldiamond 1962) as the punishing stimuli, contingent upon stuttering it has been shown that stuttering decreases dramatically. The present study has been undertaken to validate these findings with stutterers in our cultural set up and to see the possibility of delineating those variables, which might be intimately related to stuttering, affecting improvement, positively or negatively